Clinical Outcomes And Economic Burden Of Patients Having Diabetes Mellitus And Tuberculosis In Three Hospitals In Malaysia - Aweis, Daud Moalin Ishaq (2011)
The prevalence of diabetes mellitus (DM) in Malaysia is growing to the epidemic level. Since a long time increased susceptibility of diabetic patient to wide range infectious diseases including tuberculosis (TB) has been reported. This study was intended to assess the clinical outcomes and economic burden of combined DM-TB condition. The type of this study is prevalence based prospective cohort. Study patients were divided into three groups: patients with TB infection only; patients with DM only; patients with coexistence of DM and TB. Each group included 200 subjects.